Fundamentals of Social Work: analysis of the debate present at XVII ENPESS - Paula, Luciana Gonçalves Pereira de; Cardoso, Ana Clara Serpa; Freitas, Isadora das Graças; Silva, Jude de Oliveira Bento da (Argumentum, 2025)
This article quantitatively and qualitatively analyses the presence of the debate on the Fundamentals of Social Work in the annals of the XVII ENPESS, held in 2022 in Rio de Janeiro. The analysis considers the various perspectives on the understanding of the Fundamentals of Social Work. The article highlights authors who have dedicated themselves to this debate and demonstrates the varied definitions that they have constructed on the fundamentals of the profession. It points out the existence of three main trends in the discussion and, finally, presents the results of the research through an analysis that points to a paucity of output on this theme in the XVII ENPESS and signals a lack of clarity around a conception of Fundamentals among these authors.